Спростіть вираз 2(3x-4)-3(2x-5)+7 до іть вирішити.

лизанезнающая лизанезнающая    2   19.07.2022 19:10    1

Ответы
lenichk lenichk  19.07.2022 19:11

Объяснение:

2(3х - 4) - 3(2х - 5) + 7 =

6х - 8 - 6х + 15 + 7 =

(6х - 6х) + (-8 + 15 + 7) =

0 + 14 = 14

ПОКАЗАТЬ ОТВЕТЫ
OBOShh OBOShh  19.07.2022 19:11

***

раскроем скобки

2(3х - 4) - 3(2х - 5) + 7 =

(2 · 3х) - (2 · 4) - (3 · 2х) - ( (-3) · (-5) ) + 7 =

6х - 8 - 6х + 15 + 7 =

6х + 14 - 6х = 0 + 14 =

14

ответ: 14

ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Алгебра

Популярные вопросы